Financial Literacy and Entrepreneurial Intention: The Mediating Role of Motivational Factor - Ida Ida; Henky Lisan Suwarno (International Journal of Economics, Commerce, and Management, 2025)
Increasing the rate of entrepreneurship is crucial for promoting inclusive and sustainable economic growth, as it serves as a vital component of the economy and job creation. This study aims to analyze the factors that influence entrepreneurial intention among Generation Z (Gen Z), with a specific focus on financial literacy and motivational factors as mediating variables. A total of 114 Gen Z individuals domiciled in West Java participated as respondents in this study. The research employed quantitative methods with data collection through questionnaires and data analysis techniques using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings reveal that financial literacy does not have a significant direct effect on entrepreneurial intention. However, motivational factors are found to play an essential mediating role, strengthening the indirect effect of financial literacy on entrepreneurial intention. Furthermore, the study shows a direct and positive relationship between motivational factors and entrepreneurial intention, as well as a direct effect of financial literacy on motivational factors. These results suggest that enhancing financial literacy alone may not be sufficient to increase entrepreneurial intention without the support of strong motivational drives. The implication of this study highlights the importance of designing educational curricula and training programs that not only build financial knowledge but also foster entrepreneurial motivation. Such efforts can ultimately strengthen entrepreneurial intention and contribute to sustainable economic growth. The limitation of this study lies in its focus on Gen Z respondents exclusively from West Java, which may affect the generalizability of the findings.